Comparative Analysis Of Catfish Cultivation Business Between Breeding And Spanishing (Case Study On Bolopijah Farming Group) - Satoto, Shinta Heru; Subagio, Hani; KP, Hasa Nurrohim (RSF Conference Series: Business, Management and Social Sciences, 2021)
Profit is an important part of a business because profit is one measure of business success that determines the end of a production cycle. This study seeks to analyze the structure of costs, revenues, and profits in catfish farming. Questionnaires were given to 30 respondents who are members of the Bolopijah Farmers Group, Randugowang Village, Sleman Yogyakarta. The results showed that the costs incurred in the catfish rearing system were greater than the costs in the spawning system. While the income generated in the spawning system is greater than the rearing system. The results of the R/C ratio analysis show that these two cultivation systems have an R/C ratio > 1, so it can be concluded that these two cultivation systems are still profitable and feasible to continue. However, the R/C ratio of the spawning system showed greater results than the rearing system.